2020
DOI: 10.6007/ijarbss/v10-i11/7959
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Self Efficacy with Higher Order Thinking Skills (HOTS) among Accounting Students

Abstract: Higher order thinking skills (HOTS) are one of the skills that is emphasized in the 21st century learning environment. Students with high ability in thinking skills will be able to compete and gain a place in the global market. Self-efficacy is one of the elements that can be a catalyst for the achievement of HOTS among students. Therefore, this study was conducted with the main purpose to examine the relationship between students' self-efficacy and HOTS. In addition, this study was also conducted to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…This result is consistent with previous research that also found a positive relationship between psychological factors such as mathematical self-confidence and mathematical resilience with the ability to solve HOTS problems (Aini & Andreansyah, 2023;Garak et al, 2020). Furthermore, this study supports Bandura's theory of self-efficacy in learning, which states that students' confidence in their ability to complete specific tasks, including HOTS problems, can influence their learning outcomes (Goik Leng et al, 2020;Syarifah et al, 2019). A strong Habit of Mind can enhance students' self-efficacy in mathematics, making them more confident and motivated to face the challenges of HOTS problems.…”
Section: Discussionsupporting
confidence: 80%
“…This result is consistent with previous research that also found a positive relationship between psychological factors such as mathematical self-confidence and mathematical resilience with the ability to solve HOTS problems (Aini & Andreansyah, 2023;Garak et al, 2020). Furthermore, this study supports Bandura's theory of self-efficacy in learning, which states that students' confidence in their ability to complete specific tasks, including HOTS problems, can influence their learning outcomes (Goik Leng et al, 2020;Syarifah et al, 2019). A strong Habit of Mind can enhance students' self-efficacy in mathematics, making them more confident and motivated to face the challenges of HOTS problems.…”
Section: Discussionsupporting
confidence: 80%